Canónigo Ramos: Perspectivas Históricas y Contemporáneas - Oñate Quintana, David Alejandro (2025)
This research examines the life and legacy of Canon Eudoro Antonio Ramos Romero, a central figure in the clergy of Riobamba during the 20th century, whose influence extended beyond the religious sphere to shape the social, educational, and cultural development of the Chimborazo province. Through a qualitative methodology based on documentary sources, ecclesiastical archives, and oral testimonies, the study reconstructs his pastoral trajectory across various parishes and his deep commitment to the local community. Among his most significant contributions is the donation of land for the construction of the OSCUS Center of Studies, which has played a crucial role in providing technical and humanistic education to youth in vulnerable situations. His work is contextualized within the broader framework of social and ecclesiastical transformations marked by the Second Vatican Council, which redefined the role of the clergy and its engagement with society. The thesis also explores the construction of historical memory around his figure, highlighting the importance of "sites of memory" in shaping the collective identity of Riobamba. The naming of Avenida Canónigo Ramos in his honor symbolizes public recognition of his contributions. Preserving the historical memory of figures such as Canon Ramos not only enables a deeper appreciation of the past but also strengthens the community’s sense of identity and belonging. His life exemplifies a steadfast commitment to education and social service, demonstrating how individual actions can drive societal transformation. This study seeks to contribute to the dissemination of his legacy, emphasizing his role in the history of Riobamba and his lasting impact on collective memory.